Self-Q-Switch and CW Operation of a Tunable Dual-Wavelength Er/Yb Double-Clad Fiber Laser - Ibarra Escamilla, Baldemar; Durán Sánchez, Manuel; Posada Ramírez, Berenice; Prieto Cortés, Patricia; Alvarez Tamayo, Ricardo Iván; Kuzin, Evgeny A. (2018)
Abstract: In this paper, a double-clad Er/Yb ﬁber laser with self-Q-switched and continuous wave operation depending on the pump power range is experimentally demonstrated. The linear cavity is formedononesidebyapairofcascadedtunableﬁberBragggratingsusedfortheselectionandtuning of the generated laser lines. On the opposite side, a ﬁber optical loop mirror with high birefringence ﬁber in the loop is used to adjust the intra-cavity losses to obtain dual-wavelength emission by temperaturechangesontheﬁberloop. Continuouswavedual-wavelengthlaseroperationisobtained for tunable separation of the generated laser lines in a range from 1 to 7 nm, maximum output power of 3.6 W with a pump power of 10 W and laser wavelengths linewidth of ~0.2 nm. Self-Q-switched laser pulses are obtained with low pump power in a range from 322 to 890 mW. Q-switched pulses with minimum pulse duration of ~1.5 µs and maximum pulse energy of ~3.5 µJ are obtained. Keywords: ﬁber lasers; Q-switched lasers; ﬁber Bragg gratings; Er/Yb double-clad ﬁbers; ﬁber optical loop mirror